2017
DOI: 10.1302/2046-3758.66.bjr-2016-0259.r1
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and ageing affects the migration of stem cells and this is ameliorated by transfection with CXCR4

Abstract: ObjectivesCellular movement and relocalisation are important for many physiologic properties. Local mesenchymal stem cells (MSCs) from injured tissues and circulating MSCs aid in fracture healing. Cytokines and chemokines such as Stromal cell-derived factor 1(SDF-1) and its receptor chemokine receptor type 4 (CXCR4) play important roles in maintaining mobilisation, trafficking and homing of stem cells from bone marrow to the site of injury. We investigated the differences in migration of MSCs from the femurs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Interestingly, Zhu et al (33) reported that conditioned media from PTH-treated osteoblasts and osteocytes contain soluble chemotactic factors for bone marrow mesenchymal progenitors. Many candidates could stimulate migration of progenitor cells from the vessel wall to the bone surface, including amphiregulin (33) SDF-1, (34) or MCP-1, all potent chemotactic factors for mesenchymal precursors, whose osteoblastic expression is strongly stimulated by iPTH. (35) Interestingly, we observed at day 28 an increase in MCP-1 expression in iPTH-treated bones only (Fig.…”
Section: Effects Of Ipth On the Vascular Transitional Networkmentioning
confidence: 99%
“…Interestingly, Zhu et al (33) reported that conditioned media from PTH-treated osteoblasts and osteocytes contain soluble chemotactic factors for bone marrow mesenchymal progenitors. Many candidates could stimulate migration of progenitor cells from the vessel wall to the bone surface, including amphiregulin (33) SDF-1, (34) or MCP-1, all potent chemotactic factors for mesenchymal precursors, whose osteoblastic expression is strongly stimulated by iPTH. (35) Interestingly, we observed at day 28 an increase in MCP-1 expression in iPTH-treated bones only (Fig.…”
Section: Effects Of Ipth On the Vascular Transitional Networkmentioning
confidence: 99%
“…Older rats have fewer CFUs, fewer MSCs in the bone marrow, possibly explaining the reduced yields in non‐mobilized controls and mobilized groups compared with Pitchford et al, who used young mice. Humans also show reduced CFUs with ageing and a recent study also showed an age relationship with CXCR4 dependent migration and hence the effect of antagonism of the CXCR4‐SDF1 axis may also reduce with age. Most of the studies looking at peripheral blood circulating stem cells and mobilization in animal models have used young immature animals, and therefore there may be merit in evaluating the role of age in mobilization potential.…”
Section: Discussionmentioning
confidence: 98%
“…Mesenchymal stem cells (MSC) are known to migrate to sites of injury in a response to chemical signals . Impaired recruitment of MSC to locations of bone remodeling is a proposed explanation for compromised bone formation . Unfortunately, studies involving systemic infusion of MSC have not shown that the cells are able to migrate to and engraft at fracture sites, although some have reported enhanced tissue repair despite the lack of engraftment .…”
Section: Featured Articlesmentioning
confidence: 99%
“…In these cases, they don't necessarily differentiate and replace the damaged tissue, but influence therapeutic change by migrating to the damaged tissue and mediating recovery through the action of other cell types . This mechanism of action depends on the ability of the cells to migrate to a disease site, which can be impaired in patients with severe disease . Determining ways in which we can recover or enhance the pathways that allow cells to respond to and migrate toward sites of damage could mitigate that issue.…”
mentioning
confidence: 99%